3D Solarweb: A solar cadaster in the Italian Alpine landscape - F. Nex; F. Remondino; G. Agugiaro; R. De Flippi; M. Poletti; C. Furlanello; S. Menegon; G. Dallago; S. Fontanari (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
The paper presents the research carried out in the on-going 3DSolarWeb project to test and implement a complete pipeline for the generation of a solar cadastre of building roofs located in alpine areas. The project aims at providing reliable results in a costeffective way, using (low resolution) available data and new aerial imagery acquisitions as input. The environmental context is digitally represented using already existing low resolution LiDAR data (1–2 m resolution), while the urban area is modelled using high resolution aerial images (10–20 cm GSD) and photogrammetric DSM. Reliable models and algorithms for the estimation of the incoming sun radiance are then adopted and a WebGIS is set up for the interactive calculation of the photovoltaic (PV) potential in a raster-based form. The paper summarizes the entire pipeline and the results (Figure 1) achieved on the test areas to show the potentialities of the method and the web-based service.